Determining the contribution of online corporate communication to brand reputation among Generation Y consumers in Vaal Region - Kunene, Sibongile (Vaal University of Technology, 2016)
ABSTRACT The internet has become one of the most powerful communication tools. Therefore, much has been written over the past few years about the rise and use of online communication, but there is still very limited research on the use of online communication by Generation Y members and corporations in an African context. Consequently, the internet has become one of the most powerful communication tool. This has led to the evolutions of the public relations discipline in keeping up with trends, embracing new opportunities and using diverse and effective communication mediums to engage with different stakeholders. This dissertation determines the contribution of online corporate communication to brand reputation amongst Generation Y members in the Vaal Region and the effect it can have on the perceived reputation of an organisation. This was done though ascertaining ways in which Generation Y in the Vaal Region (Evaton, Sebokeng and Vanderbijlpark) uses different online corporate communicate tools to engage with brands. This quantitative study used a cross-sectional descriptive research approach. Two hundred questionnaires that comprised of three sections namely: (1) demographics and sources of information, (2) online communication behaviour and (3) online reputation management were distributed amongst Generation Y members in the Vaal Region. The respondents were between the ages of 18-35, descriptive statistics such as frequencies, the mean, medium and the mode, factor analysis, t-tests and ANOVA were used to analyse the data obtained from the respondents. From the results it is evident that the growth of the internet and the development of smartphones, iPads and tablets have drastically changed the way people communicate, especially Generation Y members, thus leading brands to actively operate online. Social networking sites like Facebook, Instagram, Twitter and YouTube have taken over the technological aspect of two way interaction between customers and brands thereby influencing an organisation’s reputation. In as much as online communication has brought about change to the public relations discipline it has a detrimental impact on a company’s reputation if not managed properly. Therefore, companies that use online communication and those that do not use online communication should be aware of Generation Y’s online brand engagement, behaviour and expectation as this will have an effect on the organisations reputation when engaging with members from this group.
M. Tech. (Department of Public Relations Management, Faculty of Human Sciences), Vaal University of Technology
Keywords: Online corporate communication, Generation Y consumers, Corporate Brand; Advertising; Dissertations, Academic -- South Africa; Generation Y; Branding (Marketing); Advertising; Public relations; Communication